Unintended hedging in ambiguity experiments - Oechssler, Joerg; Roomets, Alex (Economics letters, 2014)
We describe an ambiguity hedging problem in Ellsberg experiments, where combinations of individually ambiguous bets eliminate aggregate ambiguity, and which may yield incorrect classifications of ambiguity averse subjects. We propose a new classification consistent with this hedging possibility.